Combination therapy in pulmonary arterial hypertension: recent accomplishments and future challenges - Lajoie, Annie-Christine (Pulm Circ, 2017)
Pulmonary arterial hypertension (PAH) is a life-threatening disease characterized by a progressive increase in pulmonary vascular resistance, ultimately leading to right heart failure and death. Throughout the past 20 years, numerous specific pharmacologic agents, including phosphodiesterase-5 inhibitors, endothelin receptor antagonists, prostaglandins, and more recently, soluble guanylate cyclase stimulators and selective IP prostacyclin receptor agonist, have emerged for the treatment of PAH. Early clinical trials were typically of short-term duration, comparing the effects of PAH-targeted therapies versus placebo and using exercise tolerance as the primary endpoint in most trials. A meta-analysis of these trials documented a reduction in short-term mortality of ∼40% with monotherapy. More recently, we have witnessed a progressive shift in PAH study designs using longer event-driven trials comparing the effects of upfront and sequential combination therapy on clinical worsening that is perceived as a more clinically relevant outcome measure. Recent meta-analyses also documented that combination therapy significantly reduced the risk of clinical worsening by ∼35% compared with monotherapy alone. In this review article, we will discuss the evolution of treatments and clinical trial design in the field of PAH over the past decades with a special focus on combination therapy and its current role in the management of PAH. We will also detail unresolved questions regarding the future of PAH patients’ care and the challenges of future clinical trials.